Experimental Study on the Potential Use of Pumice Breccia as Coarse Aggregate in Structural Lightweight Concrete - Widodo, Slamet; Satyarno, Iman; Tudjono, Sri (International Journal of Sustainable Construction Engineering and Technology, 2014)
Lightweight concrete application in construction works is growing rapidly in these recent years due to its advantages over ordinary concrete. In this research, pumice breccia which can be found abundantly in Indonesia is proposed to be utilized as the coarse aggregate. This study experimentally examines the effects of coarse pumice breccia aggregate content and partial replacement of portland cement with silica fume on the demoulded density and compressive strength of pumice breccia lightweight concrete. Nine groups of concrete test specimens were investigated. Test results indicate that the demoulded density of lightweight concrete tends to decrease, inversely proportional to the addition of the volume fraction of pumice aggregate into the mixes. Structural lightweight concrete can be produced when the lightweight concrete mixtures utilized the pumice breccia as coarse aggregate and its volume fraction range between 55% and 75% to the total volume of aggregate. The compressive strength of structural lightweight concrete can be improved proportionally up to 13.07% when the portland cement was partially replaced with silica fume up to 9% by weight of cement